THE MOTIVES, PREFERENCES AND TOURIST BEHAVIOR OF POLES PARTICIPATING IN ENOTOURISM TRIPS - Zawadka, Jan (Acta Scientiarum Polonorum. Oeconomia, 2018)
The main aim of the study is to show enotourism as a form of spending free time among Poles. The article presents the frequency and directions of enotourism journeys, motives of these travels and ways of spending time during this type of trips. Survey research were conducted among 223 adult Poles. The research was carried out in two stages: in May and October 2017. The questionnaire was submitted to the respondents through social media and thematic forums regarding wine and enotourism. For most respondents, it was relatively unimportant to study the secrets of viticulture or expand knowledge about wine-making and the traditions of the wine region. The possibility of traditional rest, physical activity during a trip or visiting nearby tourist attractions was definitely more important for them. It can be concluded that most Polish enotourists can be qualified as amateurs or dilettante/layman, for whom wine is an attraction that is used by the occasion and sometimes even by chance, and the decision about the place and direction of the trip is often based on a number of other conditions.